Attitudes toward affirmative action as a function of racial identity among African American college students - Schmermund, Anke; Sellers, Robert ([Place of publication not identified] Balckwell Publishers, 2001)
Variations in support for affirmative action were assessed in a sample of 181 African American college students in Massachusetts. These students generally endorsed affirmative action, and endorsement varied positively as a function of the belief that one had personally benefited from affirmative action. Aspects of racial identity, indexed by the Multidimensional Inventory of Black Identity, also predicted variations in attitudes toward affirmative action, over and above background factors and personal benefit. Consistent with realistic group conflict theory, the most influential aspects of identity were centrality (i.e., the degree to which group identity is central to personal identity), private regard (i.e., pride in the group), and an oppressed minority ideology (i.e., a viewpoint that emphasizes the similarities between African Americans and other oppressed groups).
Includes bibliographical references.
Keywords: Blacks -- Race identity -- Africa; Affirmative action programs -- Africa; Intergroup relations